Enhancement of dewatering performance of vitrinite-rich and inertinite-rich coals by surfactants: Experiment and simulation. (15th June 2022) - Ping, An; Peng, Yaoli; Xie, Guangyuan; Wang, Mengdie; Xia, Wencheng
Graphical abstract: Highlights: Non-ionic surfactants have an excellent dewatering effect on vitrinite-rich coal. Cationic surfactants have an outstanding dewatering effect on inertinite-rich coal. Surfactants can reduce the pressure required to remove water from the filter cake. Surfactants have an agglomeration effect on fine coals increasing filter cake porosity. Abstract: The high moisture content of fine coals, especially flotation clean coals has affected the production of coal processing plants for a very long time. The two main components of fine coals are vitrinite and inertinite. The percentage of these two macerals present in the coal has an impact on the dewatering process. In this paper, the influence of surfactants on the dewatering effect of two samples with different maceral contents is studied. The results demonstrate that non-ionic surfactants have an excellent dewatering effect on vitrinite-rich coal, and it reduced the filter cake moisture by 1.84%, while cationic surfactants have an outstanding dewatering effect on inertinite-rich coal, and it reduced the filter cake moisture by3.81%. For both the coals, surfactant adsorption reduces the hydrophobicity of the coal. The best dewatering effect corresponds to the lowest filtrate surface tension and the loosest filter cake structure. Surfactants can reduce the pressure required to remove water from the filter cake by lowering the surface tension of the filtrate. In addition, surfactants have an agglomeration effect on fine coals, which increases the porosity of the coal and facilitates a low-moisture product. This study will help engineers select the suitable filter aid for the maceral content of coal and contribute to the development of efficient filter aids.